Real‐time power management technique for microgrid with flexible boundaries. Issue 16 (15th June 2020) - Hu, Xiaotong; Liu, Tianqi; He, Chuan; Ma, Yiwei; Su, Yu; Yin, He; Wang, Fei; Tolbert, Leon M.; Wang, Shunliang; Liu, Yilu
Abstract : In order to diminish the impacts brought by high penetration of renewable energy on the reliability of distribution systems, some distribution networks (e.g. Chattanooga electric power board system) have deployed smart switches (SSs) to island some areas to mitigate outage losses. However, due to intermittency and sharply changing rate of renewable energy, it is likely to experience insufficient or excessive power for islanded areas. Therefore, a microgrid controller featured with flexible boundaries is proposed. With proposed microgrid controller, the microgrid can not only shrink or expand its boundaries according to current renewable energy supply, but also disconnect/connect to the main grid with a designated SS. Moreover, to ensure the microgrid controller could obtain suitable boundaries on the time scale of seconds, a real‐time power management technique with alternative generating algorithm is designed to generate all possible alternative boundaries and choose the optimal one, which is scalable to any topology. In addition, in order to maintain state of charge of batteries within a desirable range, anti‐overcharge/discharge strategies are designed. Four comprehensive experiments verify that the implementation of the microgrid controllers can realise flexible boundaries and deal with sharply changing rate of renewable generation or load on the time scale of seconds.